Ethics Education and the Role of the Symbolic Market - Everett, Jeff S. (Journal of business ethics, 2007)
This study responds to suggestions that business-school faculty are promoting distorted views of human nature and out-dated notions of ethics. Specifically, the paper examines in-depth interviews with a sample of 15 faculty centrally-positioned within the field’s symbolic market, namely, academics who completed their Ph.D. programs in the same institutional space as the editors of five top accounting journals. The paper finds that ethics are for the most part important to these individuals, but that the field’s general adherence to the neoclassical economic model creates pressures that militate against a deeper concern for and more adequate treatment of the topic.